Photoelastic analysis of stress distributions in the root–bone interface when applying various orthodontic methods to subside lower anterior crowding. (October 2018) - Chiang, Pao-Chang; Lin, Shu-Li; Liu, Ming-Jung; Fan, Kan-Hsin; Chang, Wei-Jen; Lee, Sheng-Yang; Huang, Haw-Ming
Dental crowding is a prevalent problem in modern society. Various factors, including different bracket systems and geometry of wire, influence the outcome using superelastic wire in the alignment stage of treatment. Currently, the use of light round wire instead of large-sized rectangular wire is emphasized to avoid powerful torsional stiffness. However, these guidelines lack scientific evidence for support. They have been written predominantly based on clinical experience. Therefore, the purpose of this study was to evaluate how factors such as bracket systems and wire geometry affect the stress distribution at the root–bone interface. Models using a photoelastic material (PL-3) to simulate bone tissue were fabricated. The simulated teeth were arranged as in lower anterior crowding. Then, the crowded teeth were subjected to orthodontic treatment with various types of bracket, ligating approaches using ligature wires of different sizes, shapes, and materials. Photoelastic images of the bone area of the models were obtained and compared. The results showed that wire size plays a more significant role than the material or cross-sectional shape of the wire in affecting the stress distribution at the simulated root–bone interface. The teeth ligated with a larger cross-sectional diameter of wire showed the application of excessive torque, which may cause root resorption and slow down tooth movement. These results not only demonstrate the scientific evidence backing clinical experience but also can be a useful reference for further clinical application.